Characterization of the most odor-active volatiles in fresh, hand-squeezed juice of grapefruit (Citrus paradisi Macfayden) - Büttner, Andrea; Schieberle, Peter (Journal of Agricultural and Food Chemistry, 1999)
By application of the aroma extract dilution analysis on an extract prepared from fresh grapefruit juice, 37 odor-active compounds were detected in the flavor dilution (FD) factor range of 4-256 and subsequently identified. Among them the highest odor activities (FD factors) were determined for ethyl butanoate, p-1-menthene-8-thiol, (Z)-3-hexenal, 4,5-epoxy-(E)-2-decenal, 4-mercapto-4-methylpentane-2-one, 1-heptene-3-one, and wine lactone. Besides the 5 last mentioned compounds, a total of 13 further odorants were identified for the first time as flavor constituents of grapefruit. The data confirmed results of the literature on the significant contribution of 1-p-menthene-8-thiol in grapefruit aroma but clearly showed that a certain number of further odorants are necessary to elicit the typical grapefruit flavor.
Keywords: grapefruit; flavor; 4-mercapto-4-methylpentane-2-one; 1-heptene-3-one; wine lactone; grapefruit; aroma extract dilution analysis